2010
DOI: 10.1510/icvts.2010.247080
|View full text |Cite
|
Sign up to set email alerts
|

Death in low-risk cardiac surgery: Stockholm experience

Abstract: In cardiac surgery, perioperative death in low-risk patients is uncommon, but does occur. Reports on the incidence, cause and circumstances of death in this population are rare. We analyzed the early mortality and cause of death in patients with an additive EuroSCORE≤3 who underwent cardiac surgery between 2001 and August 2009 in Stockholm. We also investigated if death could be considered preventable, and in that case, if it was due to a technical or a system error. Among 3924 low-risk patients, 15 died withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Although the reasons for mortality have been extensively studied in high-risk patients,8,9 only a few reports have analysed the reasons for and possible preventive strategies of mortality in low-risk patients undergoing coronary artery bypass grafting (CABG) 10,11. Drawing on the FIASCO study,10 we reviewed the mortality in our own low-risk CABG patient population in order to identify whether death could be considered preventable, and if so, whether it was due to a technical or system error.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reasons for mortality have been extensively studied in high-risk patients,8,9 only a few reports have analysed the reasons for and possible preventive strategies of mortality in low-risk patients undergoing coronary artery bypass grafting (CABG) 10,11. Drawing on the FIASCO study,10 we reviewed the mortality in our own low-risk CABG patient population in order to identify whether death could be considered preventable, and if so, whether it was due to a technical or system error.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, rates of early mortality within 30 days vary from 1.1% to 9% in heart surgery [11][12][13][14]. Factors increasing the rate of early morbidity and mortality include severe left ventricular dysfunction, previous MI, serious ischemic mitral regurgitation, renal failure and chronic pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative death in low-risk patients is uncommon and had not been thoroughly studied until recently [3][4][5][6][7]. Previous studies defined low--risk with a logistic EuroSCORE ≤ 2 or an additive EuroSCORE ≤ 3, and investigated whether death could be considered preventable due to a technical or system error.…”
Section: Discussionmentioning
confidence: 99%
“…Although the observed in-hospital mortality in very low-risk patients was 0.93%, the expected risk based on the EuroSCORE II was even lower (0.70), and this difference could reach statistical significance in a larger sample. Table 3 summarizes the findings of different studies analyzing death in low-risk patients and virtually 3 of them (from United Kingdom [3,4] and Sweden [5]) showed mortality rates well below 1%. The remaining 2 studies from Turkey reported similar results to ours, though they only included coronary artery bypass grafting that has a well-known lower risk of operative mortality than other types of open heart surgery [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation